Participatory songwriting in a Belgian asylum reception center: addressing challenges through embodied strategies - Reynaert, Tina; De bisschop, An; Nijs, Luc (Frontiers in Psychology, 2025)
In recent years, asylum reception centers in the Global North have emerged as distinct settings for participatory songwriting activities. Despite the growing body of research on music facilitation within these contexts, a more comprehensive exploration of challenges associated with songwriting is required, alongside the development of both conceptual frameworks and practical tools to optimize participatory songwriting facilitation. This study employed an action research approach to critically examine and enhance the music facilitation process of The Scratch Band, a songwriting project in a Belgian reception center. By analyzing preparatory notes, transcribed and annotated video recordings of rehearsals, and a reflexive diary, challenges encountered during songwriting workshops were identified and strategies were designed strategies to address them. The findings reveal three key insights: (1) the researcher-facilitator faced place-based, person-based, and procedure-based challenges; (2) embodied strategies—including soundwalks, embodied musical brainstorms, timbral improvisation and moving lyrics—fostered participant-led creativity; and (3) these embodied strategies aligned with the constraint-led approach, suggesting its potential as a framework for conceptualizing practices and designing facilitation tools. This study demonstrates the potential of action research to reflect and improve music facilitation in participatory music practices. The results offer practical implications for music facilitators, highlighting the use of embodied music strategies to address challenges in songwriting workshops with applicants for international protection.